A novel Equilibrated scheduling algorithm for multimedia transmission in Internet of Multimedia Things. (December 2020) - BOUZEBIBA, Hadjer; LEHSAINI, Mohamed
Highlights: A novel scheduling algorithm is proposed to improve the quality of service of multimedia transmission in IoMT networks. The proposed algorithm provides an efficient queue management by taking advantage of the unused memory space and stops the enqueue procedure in an overloaded case which results in reducing the total packets drop. We have experimentally demonstrated that our proposed algorithm achieves better performance in comparison with the other scheduling algorithms in terms of packet delivery ratio, average end-to-end delay and throughput. Graphical abstract: Abstract: Internet of Multimedia Things (IoMT) has recently witnessed a rapid growth in the world of new technologies that provide numerous multimedia-based services. The primary objective of this work is to develop a novel equilibrated extension of the Deficit Weighted Round Robin (DWRR) scheduling algorithm entitled EDWRR. The proposed algorithm incorporates a Medium Access Control (MAC) layer solution for the purpose of improving the Quality of Service (QoS) of multimedia transmission in IoMT networks. The results highlight the efficiency of the proposed algorithm with regards to the reduction of the packet drop rate. Moreover, the proposed algorithm provides an efficient queue management by taking advantage of the unused memory space. In addition, through the attempt to tackle the problem of overloaded queues, the proposed algorithm is able to achieve better performance in comparison with the other scheduling algorithms in terms of packet delivery ratio (PDR), average end-to-end delay and throughput.